Development of a Novel Double Antibody Sandwich Quantitative Enzyme-Linked Immunosorbent Assay for Detection of Porcine Epidemic Diarrhea Virus Antigen - Fan, Baochao; Sun, Jie; Zhu, Lin; Zhou, Jinzhu; Zhao, Yongxiang; Yu, Zhengyu; Sun, Bing; Guo, Rongli; He, Kongwang; Li, Bin (Frontiers in Veterinary Science, 2020)
Porcine epidemic diarrhea virus (PEDV) causes acute diarrhea and dehydration in sucking piglets with a high mortality rate. Here, we developed a double antibody sandwich quantitative enzyme-linked immunosorbent assay (DAS-qELISA) for detection of PEDV using a specific monoclonal antibody against PEDV N protein and anti-PEDV rabbit serum. Using DAS-qELISA, the detection limit of recombinant PEDV N protein and virus titer were approximately 1 μg/L and 102.0 TCID50/mL, respectively. A total of 90 intestinal and 237 fecal samples were then screened for the presence of PEDV using DAS-qELISA and reverse transcriptase PCR (RT-PCR). DAS-qELISA had a high specificity of 98.1% and sensitivity of 93.5%. The accuracy rate between DAS-qELISA and RT-PCR was 95.7%. More importantly, the viral antigen concentrations remained unchanged before and after one inactivated vaccine preparation by using the DAS-qELISA. These results suggest DAS-qELISA could be used for antigen detection of inactivated vaccine samples and clinical samples. It is a novel method for diagnosing diseases and evaluation of the PEDV vaccine.